Hirschsprung disease, associated syndromes and genetics: a review. Issue 1 (26th October 2007) - Amiel, J; Sproat-Emison, E; Garcia-Barcelo, M; Lantieri, F; Burzynski, G; Borrego, S; Pelet, A; Arnold, S; Miao, X; Griseri, P; Brooks, A S; Antinolo, G; et al.
Abstract : Hirschsprung disease (HSCR, aganglionic megacolon) represents the main genetic cause of functional intestinal obstruction with an incidence of 1/5000 live births. This developmental disorder is a neurocristopathy and is characterised by the absence of the enteric ganglia along a variable length of the intestine. In the last decades, the development of surgical approaches has importantly decreased mortality and morbidity which allowed the emergence of familial cases. Isolated HSCR appears to be a non-Mendelian malformation with low, sex-dependent penetrance, and variable expression according to the length of the aganglionic segment. While all Mendelian modes of inheritance have been described in syndromic HSCR, isolated HSCR stands as a model for genetic disorders with complex patterns of inheritance. The tyrosine kinase receptor RET is the major gene with both rare coding sequence mutations and/or a frequent variant located in an enhancer element predisposing to the disease. Hitherto, 10 genes and five loci have been found to be involved in HSCR development.